Development of Creative Abilities of Future Teachers - Jumayeva Mehribo (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article discusses the pedagogical foundations for the formation and development of creative competencies in future teachers. It analyzes the importance of innovative approaches, interactive methods, and independent learning activities in developing students’ creative thinking. Furthermore, the article highlights the role of problem-based situations, modern pedagogical technologies, and motivational factors in the process of developing creativity. The study also examines effective methods and approaches that contribute to the formation of a creative approach in the professional activities of future educators.